Feasibility Analysis on the Adoption of Electronic Payment on Local Retribution in Gresik Regency : (Comparative Study of Local Retribution in Surakarta City) - Alfandia, Nurlita Sukma; Ayu Kusumawardhani, Shifa (Profit: Jurnal Adminsitrasi Bisnis, 2023)
The collection of retribution for waste in Gresik Regency is experiencing problems due to limited human resources collecting retribution. These problems have an impact on payments and billing processes manually. To overcome these problems, the Department of the Environment should innovate by adopting e- payment for market service retribution for the City of Surakarta. This study uses a qualitative descriptive approach. The research focuses on applying retribution payment in the Gresik Regency and analyzing the feasibility of adopting e-payment in the Gresik Regency. The results of this study are the manual method is considered ineffective because collecting retribution payment data takes a long time and indicates illegal levies. The implementation of e-payment using the virtual account method is considered applicable because transactions can be done anywhere. Based on a SWOT analysis, E-payment is feasible to be implemented in the retribution for waste services if it pays attention to the urgency of understanding information technology from the Environmental Service and planning for mature technology adoption in collaboration with the Gresik District Communication and Information Agency, as well as stakeholder participation. To take part in the preparation of business strategies to the process of compiling e- payment technology.